2001
DOI: 10.1002/casp.632
|View full text |Cite
|
Sign up to set email alerts
|

Early impact of the BEST intervention for parents stressed by adolescent substance abuse

Abstract: Youth involvement in substance abuse can be a source of considerable distress for their parents. Unilateral family interventions have been advocated as one means by which concerned family members can be supported to assist substance‐abusing family members. To date there has been little research examining the impact of unilateral family interventions on the directly participating family members. In this study the early impact of an 8‐week parent‐group programme known as Behavioural Exchange Systems Training (BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…These include poor family management (poor use of guidelines, monitoring, rewards, discipline); harsh parenting (including physical punishment or verbal reprimands); poor parental modelling; negative child-parent relationship (including hostility, conflict); ineffective control; permissiveness; lack of parental warmth, connectedness and bonding; poor communication; favourable parent attitudes to substance use; and antisocial behaviour (Bamberg, Toumbourou, Blyth & Forer, 2001;Griffin, Botvin, Scheier, Diaz & Miller, 2002;Hawkins et al, 1992;Kumpfer, Alvarado & Whiteside, 2003;McGillicuddy et al, 2001;Stone et al, 2012 ).…”
Section: Family Environment and Substance Misusementioning
confidence: 99%
See 4 more Smart Citations
“…These include poor family management (poor use of guidelines, monitoring, rewards, discipline); harsh parenting (including physical punishment or verbal reprimands); poor parental modelling; negative child-parent relationship (including hostility, conflict); ineffective control; permissiveness; lack of parental warmth, connectedness and bonding; poor communication; favourable parent attitudes to substance use; and antisocial behaviour (Bamberg, Toumbourou, Blyth & Forer, 2001;Griffin, Botvin, Scheier, Diaz & Miller, 2002;Hawkins et al, 1992;Kumpfer, Alvarado & Whiteside, 2003;McGillicuddy et al, 2001;Stone et al, 2012 ).…”
Section: Family Environment and Substance Misusementioning
confidence: 99%
“…Treatment approaches such as Multidimensional family therapy (Liddle, 2002;Liddle et al, 2004a;2004b), Multisystemic Treatment (MST) (Henggeler et al, 1991;Henggeler, Clingempeel, Brondino & Pickrel, 2002), and Behavioural Exchange Systems Therapy (BEST) (Toumborou, Blyth, Bamberg, Bowes & Douvas, 1997;Toumbourou et al, 2001) have all rigorously demonstrated the clear advantages of involving family in the treatment of adolescent substance misuse and other behavioural problems, such as juvenile crime . Family-focused interventions, whether systemic in nature, or a combination of behavioural, cognitive-behavioural, or focused on parenting skills, parent training, parent education or counselling-oriented, have all demonstrated to have effect sizes two to nine times greater than child onlyfocused interventions (Kumpfer, Alvardo & Whiteside, 2003;Latimer et al, 2003;Liddle et al, 2004 ).…”
Section: Family-based Treatment Optionsmentioning
confidence: 99%
See 3 more Smart Citations